Aperture synthesis methods and applications to optical astronomy - Saha, Swapan K. (Astronomy and Astrophysics Library, 2011)
Over the years long baseline optical interferometry has slowly gained in importance and today it is a powerful tool. This timely book sets out to highlight the basic principles of long baseline optical interferometry. The book addresses the fundamentals of stellar interferometry with emphasis on aperture synthesis using an array of telescopes particularly at optical/IR wavelengths. It discusses the fundamentals of electromagnetic fields, wave optics, interference, diffraction, and imaging at length. There is a chapter dedicated to radio and intensity interferometry corroborating with basic mathematical steps. The basic principle of optical interferometry and its requirements, its limitations and the technical challenges it poses, are also covered in depth. Assisted by illustrations and footnotes, the book examines the basic tricks of the trade, current trends and methods, and it points to the potential of true interferometry both from the ground and space.